Making ideas "app"-en: the creation and evolution of a digital mobile resource to teach social work interviewing skills. - Turner, Denise; Landmann, Mick; Kirkland, Diane (Social Work Education, 2020)
This paper describes the processes involved in the design, delivery, and evolution of a mobile app.' The initial app' was funded by an institutional Teaching Award to update the delivery of Egan interviewing skills to social work students. The article charts the progress of development, beginning with the initial rationale for the app' and its subsequent evolution into a Motivational Interviewing resource for social workers within a designated local authority. Arguing for the increasing importance of digital resources, within social work training and practice, the article draws from theories of digital pedagogy, as well as highlighting the work of some prominent figures within this emerging field. The article is written as a collaboration between the lead author and the app' developers, who have contributed technical detail and emphasized the need for collaboration. Whilst the article touches briefly on the mechanics involved with app creation, its chief aim is to act as a guide to the practical, financial and relational aspects of development – in order that other social work practitioners and educators are inspired to progress their own ideas into innovative digital resources. To facilitate this, the article concludes with a practical list of suggestions for successful digital development.